An observational report of universal GeneXpert testing of inpatients with diagnosed or presumptive TB in the Philippines. (27th June 2020) - Thi, Aye Myat; Lee, Nathaniel; Parris, Victoria; Marin, Flora P; Roy, Lynsil; Calapis, Rugaiya W; Ariyoshi, Koya; Parry, Christopher M; Cox, Sharon E
Abstract: Background: The Philippines is a high TB and multidrug-resistant TB burden country. Although the scale-up of GeneXpert testing is occurring, the benefits of universal Xpert- Mycobacterium tuberculosis / rifampicin (MTB/RIF) testing in inpatients have not been documented. Methods: Routine GeneXpert testing irrespective of priority criteria for testing was conducted within a prospective cohort of all adults with known or presumptive TB admitted to a tertiary infectious diseases hospital in Manila. Study-specific TB diagnosis was decided upon bacteriological results, chest x-ray assessment, if already on anti-TB treatment (ATT) at admission and a cough duration of ≥2 wk. Results: Of submitted sputum samples, 87.1% (277/318) had valid acid-fast bacilli (AFB) microscopy and Xpert® MTB/RIF results. Xpert® MTB/RIF was positive in 97.7% (n = 87/89) of AFB-positive patients and 25.5% (n = 48/188) of AFB-negative patients. Bacteriological confirmation in smear negative cases not on ATT prior to admission was 25.2% (34/135). Rifampicin resistance was detected in 26/135 Xpert positive cases (19.3%), including nine who might not otherwise have been detected, representing a 53% increase in yield. Conclusion: Universal GeneXpert testing in this setting enhanced the yield of bacterial confirmation, revealing a high incidence of rifampicin resistance and suggesting a need for further investigations in Xpert-negative/smear-positive patients who may not have mycobacterial TB.